1994
DOI: 10.1111/j.1469-8137.1994.tb02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in mycorrhizal development and growth stimulation by 20 Pisolithus isolates inoculated on to Eucalyptus grandis W. Hill ex Maiden

Abstract: SUMMARYTwenty isolates of Pisolithus, covering a range of hosts, basidiocarp types and geographic locations were corapared on their ability to form mycorrhiza in vitro with Eucalyptus grandis and to stimulate scedlmg growth in vivo. There was a large \ariation between isolates in the rate of mycorrhiza! development and this was used to categorize isolates into six types. Mycorrhiza of seediings inoculated with t\'pe I isolates were the most advanced with a duallayered mantle, a fuliy-developed Hartig net and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 21 publications
3
89
1
1
Order By: Relevance
“…Both VAM and ECM fungi vary in carbon sink strength and apparently also in symbiotic effectiveness (e.g. Abbott, Robson & Gazey, 1992 ;Burgess, Dell & Malajczuk, 1994 ;Cullings, Azaro & Bruns, 1996). However, fungal isolates that perform poorly in some experiments may provide substantial benefits to plants in other trials where growing conditions are more suitable for that particular fungus (Dickson, Smith & Smith, 1999).…”
Section: Synchronised Developmentmentioning
confidence: 99%
“…Both VAM and ECM fungi vary in carbon sink strength and apparently also in symbiotic effectiveness (e.g. Abbott, Robson & Gazey, 1992 ;Burgess, Dell & Malajczuk, 1994 ;Cullings, Azaro & Bruns, 1996). However, fungal isolates that perform poorly in some experiments may provide substantial benefits to plants in other trials where growing conditions are more suitable for that particular fungus (Dickson, Smith & Smith, 1999).…”
Section: Synchronised Developmentmentioning
confidence: 99%
“…Plastic pots (2-l volume, 14-cm top diameter) were lined with plastic bags and filled with 2 kg of soil. Nutrient solutions, other than P, were applied at concentrations known to be optimum for eucalypt growth in this soil (Burgess et al, 1994, Brundrett et al, 1996. These concentrations were (mg kg −" soil) :…”
Section:   mentioning
confidence: 99%
“…Soil preparation and fertilizer additions were based on earlier glasshouse trials where responses of Eucalyptus spp. to mycorrhizal inoculation were quantified (Bougher et al, 1990 ;Burgess et al, 1994). The soil used was a Karrakatta Yellow Sand from the Spearwood Dune System north of Perth, Western Australia (soil\water 2 : 1 slurry, pH 5.4 ; Bray extractable P 2 mg P kg −" ).…”
Section:   mentioning
confidence: 99%
“…Numerous studies have shown that individual species of AM fungi, and even fungal isolates in one species, differ in their ability to promote plant growth, and that promotion of plant growth can depend on the particular matching of plant and fungal species (Johnson, 1993;Johnson and Pfleger, 1992;Johnson et al, , 1997Jansa et al, 2002). When tested on a single plant species, the fungal isolates can increase, decrease, or have little effect on plant growth (Burgess et al, 1994;Feng et al, 2001;van der Heijden and Kuyper, 2001;O'Keefe and Sylvia, 1993). This inter-and intraspecific variation makes it essential to screen for efficient AM fungi for particular host-plant species.…”
Section: Introductionmentioning
confidence: 99%